Antibacterial Activity of Cinnamomum camphora Essential Oil on Escherichia coli During Planktonic Growth and Biofilm Formation - Wang, Lei; Zhang, Kang; Zhang, Kai; Zhang, Jingyan; Fu, Jingjing; Li, Jie; Wang, Guibo; Qiu, Zhengying; Wang, Xuezhi; Li, Jianxi (Frontiers in Microbiology, 2020)
Bacterial biofilms are believed to be principal virulence factors for many localized chronic infectious diseases. Escherichia coli is one of the most common microbial pathogens and frequently causes biofilm-associated opportunistic infections, such as diarrhoea, endometritis and mastitis. Cinnamomum camphora essential oil (CCEO) has shown potential in treating intractable chronic endometritis in dairy cows. There is little scientific evidence regarding the effect of CCEO on bacterial biofilms. The objective of this study was to investigate the effect of CCEO on E. coli biofilm formation and how CCEO affects E. coli in suspension and in a biofilm. CCEO killed all clinical E. coli strains in either planktonic or biofilm state isolated from dairy cows with clinical endometritis. The minimum inhibitory concentration (MIC) for 90% of the organisms was 4.297 μL/mL, the minimum bactericidal concentration for 90% of the organisms was 6.378 μL/mL, the minimum biofilm inhibitory concentration for 90% of the organisms was 6.850 μL/mL, and the minimum biofilm eradication concentration (MBEC) for 90% of the organisms was 8.467 μL/mL. The MBECs were generally two times higher than the MICs. Flow cytometry analysis confirmed that significant bacterial killing occurred during the first 1 h after exposure to subinhibitory concentrations of CCEO. In addition, CCEO exerted a significant inhibitory effect on E. coli biofilm formation, and bacterial killing occurred during the first 30 min of exposure to subinhibitory biofilm concentrations of CCEO. The biofilm yield of E. coli was significantly reduced after CCEO treatment, along with an increased dead/live microbial ratio in biofilms compared with that in the nontreated control, as confirmed by scanning electron microscopy images and confocal laser scanning microscopy images. These data revealed that CCEO efficiently kills E. coli during planktonic growth and biofilm formation.